Ensaios de câmbio sob as perspectivas da produtividade e da competitividade - Rebelo, Helene Albuquerque (2018)
This work is composed of three independent researches, however with themes that show constancy and relation between them. The first investigation examines the long-term exchange rate, considering purchasing power parity for 25 developing countries, admitting the United States of America as the base country. To test the models, the behavior of four different price indices are observed, for the period of 1960 - 2015, with annual frequency. From the projections performed, only four combinations corroborated the theory, not being possible to prove a favorable performance for PPP. The second study evaluates the long-term exchange rate from the perspective of the Balassa-Samuelson Effect. Original from purchasing power parity, it shows that the exchange rate can be explained by the relationship between the productivities of two countries. Thus, the relative purchasing power parity and total factor productivity are evaluated by applying a new classification for productivity, where some service sectors are considered tradable goods. The database is composed of 10 pairs of countries, with the United States of America as the base country, for the period between 1980 to 2007, finding that only a few countries corroborate the Balassa-Samuelson Effect. For the first two essays, time series analyzes were used. The third search evaluates whether productivity is explained by competitiveness and if the real effective exchange rate plays a moderating role on the four competitiveness variables, since it is possible to evaluate the losses or gains of competitiveness as a function of the exchange rate. It is applied the real effective exchange rate, the total factor productivity, and the world competitiveness index for 20 countries for the period from 2001 until 2018. The results show that the real effective exchange rate is a moderating variable for all variables, but only for half of the countries evaluated. In this third paper, the empirical approach is supported in a panel data analysis. The three essays are run on the software STATA 14.